Entre Réforme Catholique et impératifs de survie : vie religieuse et activisme féminin chez les clarisses anglaises du XVIIème siècle exilées sur le continent - Claire SCHIANO-LOCURCIO (E-REA)
In Reformation England, English women who desired to live a contemplative life were forced to flee to France or to the Spanish Netherlands. Almost fifty years later, in 1609 they created the first English Poor Clares convent dedicated specifically to English women and submitted to the Tridentine Reformation. The Council of Trent promulgated new decrees that created a new model spiritual perfection for women, insisting on the ideal of claustration and submission to male authority. Does the particular situation of the English nuns influence the establishment of this new ideal of contemplative life?Within their new convents, the English Poor Clares manage cleverly to reconcile the constraints imposed by religious authorities and the daily organization of catholic revival. Nevertheless, these women will negotiate the nature of their jurisdiction to the Papacy when they feel their spiritual or temporal good is threatened. In this negotiation process, the English Poor Clares put their exiled status forward and welcome it as a distinct element of their religious identity.